(untitled) (Global Journal of Medical Research, 2019)
Welding is a blending process that involves the joining together of metals or thermoplastics. This study was aimed at assessing the status of selected biochemical parameters and hormonal profile in plasma of some roadside welders within the age range of 35-45 years who had welded with ≥20 welding rods/day for a duration of ≤10 years (experimental group one) and ≥11years (experimental group two) respectively. Five ml blood specimen was withdrawn from each of the ninety apparently healthy recruited volunteers who were categorized as control group (n=30), experimental group one (n=30) and experimental group two (n=30). The plasma obtained was used for the quantitative measurement of alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, C-reactive protein, urea, creatinine, luteinizing hormone, follicle stimulating hormone, prolactin and testosterone. The results showed no significant alterations in the mean values (p≥0.05) of all the measured biochemical and hormonal profile status in experimental group one volunteers as against that of the control group.